The ANALISIS FINANSIAL USAHA TANI MELON DI P4S LASKAR PELANGI DESA SALO DUA KECAMATAN MAIWA - Padapi, Astrini; Musdalifa, Musdalifa; Aisyah, Aisyah; Khamila, Khamila; Reni, Reni; Salman, Faris (Universitas Mataram, 2024)
As a village development facilitator, P4S Laskar Pelangi plays an active role in advancing and developing agriculture in the region. The demand for melons continues to increase as melons are a popular fruit and often consumed by the community. In addition, the climate and soil conditions suitable for melon growth allow farmers to produce melons of good quality. The success of previous melon farming has also encouraged farmers to continue to develop this business. Melon farming is important because melons have high economic value and stable demand, both in the domestic and international markets. The activity method used in this activity is a case study method with Focus Discussion Group and quantitative analysis in the form of Business Feasibility Analysis. The results of Okasa melon cultivation business use production costs which are the sum of all fixed and variable costs from Okasa melon cultivation, which is Rp. 47,350,683. The income of Okasa melon farmers is Rp 480,000,000/Year. Business income is Rp 432,649,317/Year. The BC ratio value is obtained 9, BEP is 9 which means that by reaching the production amount of 802 units, this agribusiness can return capital and ROI 216.5%. In conclusion, P4S Laskar Pelangi has succeeded in increasing farmer productivity and income through the cultivation of Okasa Japanese melons which are feasible to develop further.